Self-Esteem and Task Performance in Quality Circles - Brockner, Joel; Hess, T.M. (Academy of Management Journal, 1986)
The authors discuss research they conducted that examined the relationship between the self-esteem of quality circle group members and the effectiveness of those quality circle groups. They note that the effectiveness of quality circles has been suspected by American businesses to be responsible for the productivity of Japanese rivals. They also discuss that little research has been done on the effectiveness of these groups so their research is directed at adding to this void. They assert that a group can only be as effective as the members that make up the group and believe that self-esteem plays an important role in determining the effectiveness of an employee. Their research attempts to add to the literature that states task performance has a positive relationship with self-esteem.